Pertumbuhan Dan Adaptasi Biokimia Mangrove Rhizophora apiculata Blume., Pada Media Dengan Kondisi pH (Derajat Keasaman) yang Berbeda (University of Halu Oleo, 2023)
The purpose of this study was to determine the effect of pH (acidity) on the growth of Rhizophora apiculata Blume mangroves. to determine biochemical adaptation (vitamin C, anthocyanins and tannins). This research was an experimental research. The number of samples set was 9 mangrove seedlings. The data were analyzed by using Kaleidagraph software as well as Ms. Excel software to obtain pH (acidity) relationships between controls and treatments. The results showed that the effect of pH (acidity) obtained the highest average of relative growth rate to plant height, about 0.00475, stem diameter about 0.0147 and leaf area about 0.045; The highest biochemical adaptation of vitamin C, anthocyanins.